2020
DOI: 10.2991/jegh.k.200113.001
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Women’s Empowerment on Place of Delivery in North Eastern and Western Kenya: A Cross-sectional Analysis of the Kenya Demographic Health Survey

Abstract: KeywordsWomen's empowerment facility delivery childbirth North Eastern and Western Kenya A B S T R A C TBackground: Labor and delivery under the supervision of a skilled birth attendant have been shown to promote positive maternal and neonatal outcomes; yet, more than a third of births in Kenya occur outside a health facility. We investigated the association between measures of women's empowerment and health facility-based delivery in Northeastern and Western Kenya.Methods: Analysis of 2014 Kenya Demographic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 37 publications
1
7
1
Order By: Relevance
“…Several studies have shown that women's attitude toward violence is associated with higher women empowerment and decision-making abilities and led to better access and utilization of ANC, PNC, and institutional delivery (27)(28)(29)(30). However, in our study, it was only associated with having adequate ANC at both individual and community levels and PNC at the individual level.…”
Section: Discussioncontrasting
confidence: 71%
“…Several studies have shown that women's attitude toward violence is associated with higher women empowerment and decision-making abilities and led to better access and utilization of ANC, PNC, and institutional delivery (27)(28)(29)(30). However, in our study, it was only associated with having adequate ANC at both individual and community levels and PNC at the individual level.…”
Section: Discussioncontrasting
confidence: 71%
“…Emergence of women owned enterprise in Kenya has been on a growth trajectory since the launch of vision 2030 in the year 2008. This was in line with the international gender -focused commitments under the UN's Sustainable Development Goal 5 (SDG 5) which advocates for gender equality and girl child empowerment by 2030 (Anderson, Chebet, Asaolu, Bell &Ehiri, 2020). According to (Okello, 2020) approximately 40% of Kenyan women living urban centers are empowered compared to 22% who live in rural areas.…”
Section: Introductionmentioning
confidence: 55%
“…Access to high quality care during pregnancy, labour, delivery, and post-partum period has been shown to promote positive maternal and neonatal outcomes and very critical to reducing maternal and neonatal mortality. 8 This need can be addressed by an increase in access to institutional deliveries under the care of a skilled birth attendant. 9 Access to skilled birth care has been a challenge in developing countries, especially in rural areas of Kenya.…”
Section: Discussionmentioning
confidence: 99%